Evaluation of Master Education Program in Educational Administration Graduate School (Revised 2019) Thonburi University: Evaluation of Master Education Program in Educational Administration Graduate School (Revised 2019) Thonburi University - Indrangkura Na Ayudthya, Pathomporn; Kuprasert, Nitsinee; Trisin, Suthathip (RATANABUTH JOURNAL, 2024)
The purpose of this research is to evaluate the master education program in educational administration graduate school (Revised 2019) Thonburi University By using the CIPPIEST Model. The total curriculum at population is 212 people, divided into 5 groups: such as graduates, students, instructors, administrators, and stakeholders. Collect research data such as a questionnaire. The data analysis used frequency distribution, percentage, mean, and standard deviation. From the research results it was found that the overall evaluation results were appropriate at a high level ( = 4.50, S.D. = 0.64). The Context Evaluation ( = 4.69, S.D. = 0.52) and Process Evaluation ( = 4.67, S.D. = 0.55) were at the highest level. The suitability assessment results are followed by the Impact Evaluation ( = 4.49, S.D. = 0.66), Transportability Evaluation ( = 4.48, S.D. = 0.65), Effectiveness Evaluation ( = 4.46, S.D. = 0.65), Sustainability Evaluation ( = 4.46, S.D. = 0.70), Product Evaluation ( = 4.37, S.D. = 0.69) and Input Evaluation ( = 4.35, S.D. = 0.73) were at a high level. The Input Evaluation was the aspect with the lowest average.